(untitled) (LACCEI, 2024)
This work describes a project designed for teaching fluid mechanics content to engineering students and advanced students (academic internships) of the industrial design career of the Faculty of Architecture and Urbanism of the University of Buenos Aires (FADU- UBA). This project approach is to adhere to constructivist theories postulates, to the guidelines of the TPACK group and to the principles of project didactics (achieve an integrative, personalized, experiential, synthesizing, systematizing, conducive to the design process, participatory and selective teaching). It is considered strategic for 21st century engineering education to train students in creative thinking, train them to think about the new, about what is possible or what can be, enhancing their creativity in interdisciplinary work groups through academic activities that allow them to enhance their capacities thanks to the scientific knowledge acquired and the use of available technological tools. A simple Stokes device (design and instrumentation) is presented and a series of experiments in the range of 0.2 Re 10, which allow active learning of core concepts of fluid mechanics such as: deviation from sphericity of Stokes’ law, the consequences of working with non-infinite flows, the sensitivity of the drag force to different flow patterns -particularly when the role of viscosity becomes predominant as the Re number is reduced-, the importance of the shape, the size, the relative orientation of the object to the flow direction, the surface treatment of the objects (whether natural or artificial), the mechanisms to reduce the drag force.